Effects of omega-3 fatty acids in prevention of early preterm delivery: a systematic review and meta-analysis of randomized studies. (March 2016) - Kar, Sumit; Wong, Min; Rogozinska, Ewelina; Thangaratinam, Shakila
Abstract: Objective: Preterm birth continues to be the one of the leading causes of infant deaths worldwide. There is a need for effective, easily available, safe and acceptable interventions to prevent preterm delivery, especially before 34 weeks of gestation. Omega-3 fatty acids such as EPA (eicosapentanoic acid) and DHA (docosahexanoic acid) are available as over the counter nutritional supplements, and are taken by women to improve pregnancy outcomes, without any clear recommendations. We undertook a systematic review to assess the effects of omega-3 fatty acids on early (<34 weeks) and any (<37 weeks) preterm delivery. Methods: We searched MEDLINE, EMBASE and Cochrane Library from inception to 2014 without any language restrictions. Study selection, quality assessment and data extraction were done by two independent reviewers. Results were summarized as relative risks and 95% confidence intervals for dichotomous outcomes and mean differences for continuous outcomes. Results: Of the nine included trials (5980 women), six (4193 women) evaluated the effects of omega-3 fatty acids on early preterm delivery. The risk of early preterm delivery was reduced by 58% (RR 0.42; 95% CI 0.27–0.66; I 2  = 0%; p  = 0.0002) and any preterm delivery by 17% (RR 0.83; 95% CI 0.70–0.98; I 2  = 0%; p  = 0.03) with the intervention. There was a significant increase in the mean gestational age by 1.95 weeks (95% CI 0.42–3.48 weeks; I 2  = 0.47; p  = 0.01) and mean birth weight by 122.1 g (95% CI 47.4–196.8; I 2  = 0.84; p  = 0.001) in the intervention group compared to the controls. Subgroup analysis showed no significant differences in the effects between the groups according to the risk status, dose and timing of the intervention. Conclusion: Omega-3 fatty acids are effective in preventing early and any preterm delivery. The intervention is simple and easily available and has the potential to influence population based strategies in the prevention of preterm birth.